Walking on the water : reading Mt. 14:22-33 in the light of its Wirkungsgeschichte - Nicholls, Rachel. (Biblical Interpretation Series, 2008)
The concept of Wirkungsgeschichte is gaining ground in New Testament Studies. It involves the gathering of diverse interpretations of a text, but can it offer significant exegetical results or is it merely a form of cultural stamp collecting? This book explores the background of Wirkungsgeschichte in the philosophy of Hans-Georg Gadamer and applies the theory to a single pericope, Mt 14:22-33. Traditional historical and literary examinations of this story are brought into conversation with six works of art and a number of nineteenth century theological texts. The result is an enriched interpretation which fruitfully alerts us to the narrowness of the vision of our own time and place.